A Lesson Learn from Empowerment Program of Integrated Cassava-Tapioca Agroindustry Actors in Pati District, Indonesia - Eva Banowati (Indonesian Journal of Geography, 2020)
Frequently, empowering models for cassava farmers is programmed by government, but unsuitable to socio-geographic conditions, such as in Pati District. This study was aimed to depict social knowledge and lesson learn of cassava-tapioca agroindustry actors, and to understand the farmers’ acceptance, before and after the empowering program. The cassava farmer’s and tapioca producer’s knowledge and lesson learn were collected from 35 farmers and 19 tapioca producers.  After empowering program, farmers asked to cultivate Cassesart cassava variety (UJ-5). However, the UJ-5 productivity that was planted in 65.40 Ha were declined. While, tapioca industries were also not directly increased farmers’ welfare. Farmers’ perspective in farming process was not changed after empowerment programs. Thirty-four farmers were not ready to build up new information. While, 16 from 19 tapioca producers (84.21%) object to improve labor quality and welfare. The founded result was associated with conventional farming practices, low price product and education background in Pati District, and was increasingly weakened by limited knowledge transfer of modern farming.